Optimisation of customer satisfaction index model for business hall of operator. (21st April 2020) - Wang, Wanru; Liu, Xinxiong; Su, Yuhan
Business hall plays an important role in telecom operator's service. Modelling the customer satisfaction of the service provided by business hall is of help for telecom operators to improve their service quality. Traditional customer satisfaction models are too abstract and general, which makes the satisfaction analysis not precise enough to model the satisfaction index of a specific service. This paper focuses on modelling customer satisfaction of service provided by the business hall. An optimisation process on traditional TCSI model was conducted based on the data acquired from questionnaire survey. Based on the optimised model, suggestions about designing business hall at current time are proposed.